Digital Marketing: Stimulus Ekonomi Pasca Pandemi Bagi UMKM - Muhammad Fathul Ula (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2022)
The Covid-19 pandemic has caused a decline in the economy and activity in various sectors and regions in Indonesia. Although the economic shock caused by the Covid-19 pandemic has gradually subsided as the domestic financial market is stable and several economic sectors are booming.. This study aims to determine the recovery strategy implemented by MSMEs after the Covid-19 pandemic in Blitar Regency. The research method used is qualitative research with data collection techniques through observation and interviews. The results of this study indicate that the business recovery strategy carried out by MSMEs in Blitar Regency after the Covid-19 pandemic includes strengthening resources in terms of services and strengthening resources in the form of technology-based marketing or digital marketing. With this strategy, MSMEs are able to restore their businesses in terms of income, although they have not fully recovered.